2020
DOI: 10.3390/nu12103028
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Its Inverse Relationship with Gastric Cancer: An Ecological Study

Abstract: Coffee is the second most popular drink worldwide, and it has various components with antioxidant and antitumor properties. Due to its chemical composition, it could act as an antitumor substance in the gastrointestinal tract. The objective of this study was to explore the relationship between coffee consumption and the incidence/mortality of stomach cancer in the highest-consuming countries. An ecological study using Spearman's correlation coefficient was performed. The WorldAtlas's dataset of coffee consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Second, soybean and soy products also included saponins, which were reported as an antitumor ingredient ( 27 ). Similar to other studies, our research has shown that a higher consumption of coffee and dairy products could decrease the risk of gastric cancer ( 28 , 29 ). There were several mechanisms to explain this association: (1) coffee was a mix of bioactive compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Second, soybean and soy products also included saponins, which were reported as an antitumor ingredient ( 27 ). Similar to other studies, our research has shown that a higher consumption of coffee and dairy products could decrease the risk of gastric cancer ( 28 , 29 ). There were several mechanisms to explain this association: (1) coffee was a mix of bioactive compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Several prior clinical studies suggested the cancer protective effects of coffee consumption [10,18,19]. The concordant association of coffee consumption with protection from gastric cancer, hepatic cancer, breast cancer, and thyroid cancer has been reported in both Western and Asian studies [10,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 89%
“…The risk of gastric cancer was found to be lower among coffee consumers in a meta-analysis of case-control studies (RR = 0.85, 95% CI = 0.77-0.95) [18]. In an ecological study, countries with high coffee consumption showed a decreased incidence and mortality of gastric cancer compared to countries with lower coffee consumption (Spearman's correlation r = −0.5984, p = 0.0016) [19]. The incidence of hepatic cancer also showed an inverse association with coffee consumption in a meta-analysis study in Japan (RR = 0.50, 95% CI = 0.38-0.66, p < 0.001) [20].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, our ndings are also related to Alzheimer's disease, colorectal cancer, intellectual disability, melanoma, lung cancer, cardiovascular disease. Interestingly, there is evidence that these diseases are related to coffee consumption (5,55).…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2 polymorphism changes the risk of gastric cancer (53), and ARPC2 plays an analgesic effect in gastric cancer, providing a new target for gastric cancer treatment (54). It is worth noting that the relationship between gastric cancer and coffee consumption has also been con rmed, and coffee may have a potentially bene cial effect on the incidence and mortality of gastric cancer (55). Moreover, our ndings are also related to Alzheimer's disease, colorectal cancer, intellectual disability, melanoma, lung cancer, cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%